Do they truly care? perceived organizational support, psychological well-being and the mediating role of internalized stigma among portuguese workers - Guedes, Mariana Fernandes de Faria (2024)
Background: Recently, mental health and employee well-being have become a growing concern within organizations. However, research on the impact of organizational support on workers' psychological well-being remains relatively limited, and studies on the potential experience of stigmatization in the workplace are even scarcer, highlighting the need for further exploration of this phenomenon. Objectives: To investigate how the perception of organizational support (POS) influences the psychological well-being (PWB) of Portuguese workers. Additionally, to propose a model in which internalized stigma mediates the relationship between POS and PWB in workers with a mental health condition. Method: After informed consent, two correlational studies were conducted. In Study 1, measures of POS and PWB were applied to 278 workers (219 women and 58 men, aged between 18 and 66 years [M=37.05, SD=13.18]). The sample for Study 2 involved 109 workers (92 women and 17 men, aged between 18 and 63 years [M=36.39, SD=12.93]), who were also assessed for internalized stigma (ISMI). Results: The results of Study 1 revealed a significant positive relationship between POS and PWB, indicating that workers who perceive greater organizational support report higher psychological well-being. The results of Study 2 showed that ISMI was negatively associated with PWB, but did not mediate the relationship between POS and PWB. Conclusion: These findings highlight the negative impact of the stigmatization experience on the psychological well-being of workers with mental health conditions. Future research should investigate other factors that might influence the relationship between POS and ISMI. Practical implications include the development of organizational interventions to strengthen support systems and combat the internalization of stigma related to mental health.